Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3389/fpls.2014.00489
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of the plant-specific hybrid glycine-rich protein (HyGRP) genes in cereals

Abstract: Plant-specific hybrid proline- or glycine-rich proteins (HyP/GRPs) are involved in diverse gene functions including plant development and responses to biotic and abiotic stresses. The quantitative trait locus, qLTG3-1, enhances seed germination in rice under low-temperature conditions and encodes a member with a glycine-rich motif of the HyP/GRP family. The function of this gene may be related to the weakening of tissue covering the embryo during seed germination. In the present study, the diversification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
(70 reference statements)
3
6
0
1
Order By: Relevance
“…The qLTG3‐1 protein has two conserved domains, a glycine‐rich protein (GRP) motif and a lipid transfer protein (LTP) motif (Fujino et al ., ). qLTG3‐1 and its orthologs are conserved among rice, Brachypodium , sorghum, maize, and dicots such as Arabidopsis, and orthologous genes have a conserved function during seed germination (Fujino et al ., ; Xu et al ., ). GRP domains are functionally conserved in plants, and many genes coding for those domains are involved in cold signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The qLTG3‐1 protein has two conserved domains, a glycine‐rich protein (GRP) motif and a lipid transfer protein (LTP) motif (Fujino et al ., ). qLTG3‐1 and its orthologs are conserved among rice, Brachypodium , sorghum, maize, and dicots such as Arabidopsis, and orthologous genes have a conserved function during seed germination (Fujino et al ., ; Xu et al ., ). GRP domains are functionally conserved in plants, and many genes coding for those domains are involved in cold signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Further diversification analysis of the HyGRP gene family in five monocots, namely rice, barley, brachypodium, maize and sorghum, indicated that the HyGRP gene family was formed in the ancestral genome before the divergence of these species. The conserved collinearity of chromosomal regions around qLTG3-1 and its orthologs implies that their functions in seed germination are conserved [ 45 ]. In addition, studies indicated that mutation of PME48 , a member of the pectin esterase family, would cause a significant delay in imbibition and germination of pollen grains in Arabidopsis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protein properties and domain analyses were carried out using SMART database (http://smart.embl-heidelberg.de/). The rice genes that homologous to OsR3L1 referenced to the previous study (Fujino et al, 2014) and corresponding amino acid (aa) sequences were downloaded from RAP-DB database (https://rapdb.dna.affrc.go.jp/). The multiple sequence alignments of the 20 rice HyPRPs aa sequences were performed by jalview software, followed by phylogenetic tree generation using MEGA-X software.…”
Section: Bioinformatics Analysis Of Sequencementioning
confidence: 99%
“…The rice genome‐wide expression profiles of the OsHyP/GRP family have been investigated (Fujino, Obara, & Sato, 2014); however, the functions of most family members remain unknown. OsHyPRP06 , referred to as RCc3‐like1 ( R3L1 ) in our study, was discovered when roots were treated with gibberellin (GA 3 ) and indole acetic acid (IAA) exhibited marked changes in expression (this preliminary experiment was not published).…”
Section: Introductionmentioning
confidence: 99%